Beyond the crime-terror nexus: socio-economic status, violent crimes and terrorism. Issue 3 (18th September 2017) - Ljujic, Vanja; van Prooijen, Jan Willem; Weerman, Frank
Abstract : Purpose: The literature on terrorism suggests a strong link between criminal offending and terrorism – the crime-terror nexus. Building upon a strain theory perspective, the purpose of this paper is to suggest that devalued socio-economic status (i.e. limited education and unemployment) and criminal past define the pool of people from which violent and terror offenders may be recruited. Design/methodology/approach: The current study compares three sources of data on educational and employment characteristics of violent and terror offenders: Dutch statistical data (CBS) including the Police Recognition System (HKS) on violent criminals, the findings on jihadist networks and the open access on European terrorists. Findings: The majority of Dutch violent offenders, foreign fighters and European terrorists have only completed secondary school (or lower) and were unemployed in the year of offending. Half of recent European terrorists had previously been involved in violent crimes and/or had joined jihadi groups abroad. Research limitations/implications: One limitation of the study concerns the exploratory use of secondary and open-access data. While it was impossible to establish causality with the current methodology, these findings highlight the background conditions under which violent and terrorist crime can originate, and suggest one of the mechanisms that shapes the crime-terror nexus. Future research would benefit from more work identifying the causal antecedents to terrorism. Practical implications: Whether relative deprivation is a direct cause or merely an amplifying factor in criminal motivation needs to be scrutinized in future research. However, its consideration may have great implications for policy and law enforcement agencies. Social implications: An individual's desire to improve status and personal significance by the virtue of illegal activity may be particularly salient in the context of cultural polarization, which manifests as decreased trust and loyalty toward national laws and institutions. Parallel to preventive and security measures, it may be worthwhile to encourage multicultural associations and community networks in support of mutual (interethnic and interreligious) understanding. Originality/value: The paper explores one of the oldest factors that has been suspected of leading to terrorism in lack of economic or educational opportunity. However, the paper also offers a new perspective on how these factors may relate to participation in terrorism. Rather than claiming these factors directly cause terrorism, the authors take a strain theory perspective to argue that these strains induce fewer opportunities to engage in terrorism and provide individuals with the skills/strength to resist de-radicalization or counter-radicalization.